'Defend the Ten': Everyday dissensus against the slow spoiling of Lambeth's libraries. (October 2020) - Penny, Joe
In April 2016, 200 people in the London Borough of Lambeth occupied Carnegie Library, forcibly preventing its closure by a local council rolling-out deep austerity measures. The nine-day occupation was a high-point of 15 months of struggle to 'Defend the Ten' libraries in Lambeth against an austerity agenda the council sought to smoothly administer. Through an in-depth account of the struggle, this paper tells a story of the occupation foregrounding the protracted process and persistent interventions that led up to it. In doing so, it makes two contributions to critical geographical literatures on post-crisis austerity, responding to calls for rich, processual, and multi-scalar accounts of how austerity measures are downloaded and rolled-out, as well as experienced and resisted in everyday and undecided ways. First, going beyond an account of austerity as a fiscal policy imposed on cities from above, the paper makes visible the everyday spatial violence of austerity that is rolled-out, experienced, and resisted as a slow spoiling of social infrastructure. Second, it makes sense of the ambivalent (post)politics of austerity, developing an account of everyday dissensus to reveal mundane non-evental ruptures and the emergence of demands for real democracy in a context of closure shaped by forces of dispossession.